Assessment of Novel Long‐Lasting Ceria‐Stabilized Zirconia‐Based Ceramics with Different Surface Topographies as Implant Materials. (4th August 2017) - Altmann, Brigitte; Karygianni, Lamprini; Al‐Ahmad, Ali; Butz, Frank; Bächle, Maria; Adolfsson, Erik; Fürderer, Tobias; Courtois, Nicolas; Palmero, Paola; Follo, Marie; Chevalier, Jérôme; Steinberg, Thorsten; et al.
Abstract: The development of long‐lasting zirconia‐based ceramics for implants, which are not prone to hydrothermal aging, is not satisfactorily solved. Therefore, this study is conceived as an overall evaluation screening of novel ceria‐stabilized zirconia–alumina–aluminate composite ceramics (ZA8 Sr8 ‐Ce11) with different surface topographies for use in clinical applications. Ceria‐stabilized zirconia is chosen as the matrix for the composite material, due to its lower susceptibility to aging than yttria‐stabilized zirconia (3Y‐TZP). This assessment is carried out on three preclinical investigation levels, indicating an overall biocompatibility of ceria‐stabilized zirconia‐based ceramics, both in vitro and in vivo. Long‐term attachment and mineralized extracellular matrix (ECM) deposition of primary osteoblasts are the most distinct on porous ZA8 Sr8 ‐Ce11p surfaces, while ECM attachment on 3Y‐TZP and ZA8 Sr8 ‐Ce11 with compact surface texture is poor. In this regard, the animal study confirms the porous ZA8 Sr8 ‐Ce11p to be the most favorable material, showing the highest bone‐to‐implant contact values and implant stability post implantation in comparison with control groups. Moreover, the microbiological evaluation reveals no favoritism of biofilm formation on the porous ZA8 Sr8 ‐Ce11p when compared to a smooth control surface. Hence, together with the in vitro in vivo assessment analogy, the promising clinical potential of this novel ZA8 Sr8 ‐Ce11 as an implant material is demonstrated. Abstract : An overall evaluation screening of a novel ceria‐stabilized zirconia–alumina–aluminate composite ceramic with different surface topographies for use in clinical applications is presented. By assessing three preclinical investigation levels, namely human cell cultures, an animal model, and salivary bacteria, the promising clinical potential of this novel composite ceramic in combination with a porous surface structure as an implant material is demonstrated.